The Fundamental Skills and Deconstructed Sub-Steps of Pediatric Cardiopulmonary Bypass. - Centner, Isabel; Searles, Bruce; Riley, Jeffrey; Aiash, Hani; Darling, Edward (Journal of Extra-Corporeal Technology, 2021)
Perfusion education programs use simulation to provide students with clinical skills prior to entering the operating room. To teach the psychomotor execution of skills in a simulation lab requires a list of validated skills and deconstructed substeps to fully optimize adult learning. A list of the fundamental skills of adult cardiopulmonary bypass (CPB) was recently published; however, no defined list exists regarding pediatric CPB skills. The purpose of this survey is to form a definitive list of skills fundamental to pediatric CPB. A survey of 23 proposed pediatric CPB clinical skills and 291 proposed skill sub-steps was developed. Proposed pediatric CPB skills were evaluated using an established frequency and harm index. If the skill is performed .50% of the time (frequency), and if .50% believe that if the skill is performed incorrectly patient harm is probable (risk), then the skill is accepted as fundamental. The survey content was validated by subject matter experts and then distributed to practicing perfusionists between September 2020 and December 2020. Of the 125 survey respondents, 57.9% had 10 or more years in the field. 35.2% of respondents are American Society of Extracorporeal Technology (AmSECT) Fellows of Pediatric Perfusion (FPP) and pediatric CPB represents .50% of the annual caseload for 69.7% of respondents. 22 of the 23 proposed skills were accepted as fundamental in the conduct of pediatric CPB and 258 of the 291 proposed sub-steps associated with CPB skills were accepted as integral to skill performance. By surveying practicing pediatric perfusionists, this study identifies 22 skills as fundamental to the safe execution of pediatric CPB. In addition, skill sub-elements were identified as necessary for skill execution. This knowledge will assist perfusion programs in developing a pediatric simulation curriculum that matches current clinical execution of pediatric skills.